IMPACT OF THE CHARACTERISTICS OF OVERHEAD GROUND WIRES ON THE CURRENT REDUCTION FACTOR, AND THEIR EFFECT ON THE CHANGE OF GROUNDING SYSTEM POTENTIAL - Havranek, Mario; Strinić, Tomislav; Knežević, Goran (Journal of Energy Technology, 2024)
This paper shows the impact of the characteristics of overhead ground wires on the change of grounding system potential in a power system substation during a single line to ground fault. The touch and step voltages can be affected by changing the overhead ground wire radius. The calculation of the current reduction factor depending on the size of the overhead ground wire is also presented. Furthermore, simulations of the grounding system potential, the surface potential as well as the touch and step voltages of a study case have been made using CYMGRD simulation software, which has implemented the IEEE 80-2000 standard (IEEE Guide for Safety in AC Substation Grounding). The power system substation observed in the simulation includes two incoming 110 kV transmission lines with two 110 kV bus bars as well as 35 kV and 10 kV bus bars. The entire grounding system of the substation is comprised of a conducting net aligned horizontally, and mutually interconnected by vertically placed conducting rods. The simulations performed show the change of the observed potential values for a given size of the overhead ground wire. In order to determine the maximum fault current that can occur in the observedsubstation (which is needed for calculation of the substation ground potential), a single-phase short circuit is simulated on the 110 kV bus bars, using the simulation software DIgSILENT Power Factory.